Mountaineering Chronicles: Exploring Climbers’ Experiences on the Ascents of Mount Everest and Mount Annapurna - Gautam, Pragya (Mindscape: A Journal of English & Cultural Studies, 2023)
Mountaineering possesses an inherent allure that captivates individuals invoking a deep fascination within the human psyche and mountaineering narratives demonstrate that the enthralling nature of this adventure sport brings a sense of inner peace and contentment to climbers’ lives. By ascending towering peaks like Mount Everest and Mount Annapurna, they establish a profound connection with nature, pushing one’s physical and mental boundaries, and acquiring heightened self-awareness and understanding of the human condition. Furthermore, mountaineering is regarded as a source of knowledge, power, purity, and faith. Despite the inherent risk, the reward of experiencing sublimity at the summit is worthwhile. Climbers passionately strive for a sense of fulfillment that can only be attained by reaching the top of the mountain, a world apart from everyday life.